Since we know an isosceles triangle has 2 congruent sides we can know that the both equations can be set up as [tex]7y-3=5y+3 [/tex]. First, We combine like terms [tex]7y-3-5y=5y+3-5y[/tex]. The new equation is [tex]2y-3=3[/tex]. We do the inverse operation of subtracting 3 which is adding 3, we add 3 to both sides of the equation. The equation is now simplified as [tex]2y=6
[/tex] because we added 3 to both of the sides. Finally, we do the inverse operation of multiplying by the known coefficient of 2y which is 2, we end up dividing both sides by 2 which ends up with the equation y=6. Thus, we can conclude that y is the length of x and y which is also equal to 3.